A novel temperature-humidity index-based model for evaluating semen characteristics in Thai native roosters under tropical conditions - Wuttigrai Boonkum; Vibuntita Chankitisakul; Jiraporn Juiputta (Poultry Science, 2025)
Temperature and relative humidity indices (THIs) are widely used to study the effects of heat stress on reduced poultry production traits. However, a suitable THI for reproductive traits has not yet been established. This study aimed to develop a novel THI to predict semen traits in native roosters using regression analysis. A total of 242 Thai native grandparent roosters (Pradu Hang Dum) aged 30 weeks were used. Semen was collected weekly for 1 year to assess parameters, including semen volume, mass motility, and sperm concentration. To simplify the evaluation of semen traits, a composite measure termed the ''semen index'' was developed. This index was calculated by summing the Z-scores of the volume, mass, and concentration of each sample. Simple regression analysis was performed using several statistical criteria to identify the optimal THI function for the dataset and determine the THI threshold that influences changes in semen characteristics. The results indicated that the newly developed THI function (THI_F) offered a better fit for predicting the onset of heat stress than the original THI1, particularly at a THI threshold of 76. The improved fit of THI_F, as demonstrated by the lower values of the sum of squared errors, Akaike information criterion, and Bayesian information criterion, suggests that it provides a more reliable indication of thermal stress affecting reproductive performance. Therefore, the newly developed THI function is a more precise tool for evaluating the effects of thermal stress. This improved index has important applications in genetic selection and breeding strategies aimed at enhancing heat tolerance and reproductive performance in livestock, particularly for improving the resilience of poultry to heat stress, which is crucial for sustaining productivity under challenging environmental conditions.